PEMBELAJARAN MENULIS PUISI MENGGUNAKAN MODEL REASONING AND PROBLEM SOLVING UNTUK MEMBERI PENGUATAN PROFIL PELAJAR PANCASILA DI KELAS VIII SMPN 12 BANDUNG - Lia Indriani Suryanto; Panca Pertiwi Hidayati; Adi Rustandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to examine the effectiveness of using the reasoning and problem solving model in learning poetry writing skills for class VIII students at SMPN 12 Bandung. Lack of mastery in writing ideas and messages in poetry is often encountered, while writing poetry is one of the writing skills that students are interested in. The research method used was a quantitative experiment, involving an experimental class and a control class. The data obtained from the pretest and posttest results of both classes were processed using descriptive statistics. The analysis results showed that the experimental class, which received learning using the reasoning and problem solving model, had a minimum pretest score of 28 and a maximum posttest score of 92. While the control class had a minimum pretest value of 24 and a maximum posttest value of 72. The average value of the experimental class was 68, while the control class was 42.13. From the results of the Wilcoxon signed-rank test, it was found that in the experimental class there was 1 student who experienced a decrease in learning outcomes, 28 students experienced an increase, and 1 student who had the same score on the pretest and posttest. Whereas in the control class, there were 4 students who experienced a decrease in learning outcomes, 17 students experienced an increase, and 9 students who had the same score on the pretest and posttest. Based on the results of this study, it can be concluded that learning using the reasoning and problem solving model can effectively improve the ability to write poetry of class VIII students at SMPN 12 Bandung. This contributes to the strengthening of the Pancasila learner profile.